The impact of certain pre-competition psychological pressures on the athletic performance of football players - Amenellah, rachid (sports creativity, 2025)
Psychological stress remains a topic of considerable research and debate due to its detrimental effects on individuals and society as a whole. Prolonged stress, particularly in cases of negative coping mechanisms, can lead to a severe and sustained emotional response, as well as physical, psychological, and behavioral complications that can disrupt an athlete's usual performance during training. It's important to note that the impact of this stress depends on personality traits, including frustration tolerance, resilience, and optimism.